Les droits sexuels des personnes handicapées: réflexion sur le développement du droit international - Mona Paré (Genre, Sexualité et Société, 2018)
Interest in the sexuality of persons with disabilities is growing and research improves our understanding of issues in this regard. This leads us to a reflection on the definition of sexual rights in international law, and the way in which sexual rights of persons with disabilities are understood. Examining existing norms leads to the conclusion that despite developments in this area, sexual rights remain largely limited to the field of health, and this has not changed with the adoption of the Convention on the Rights of Persons with Disabilities (CRPD). The limited claims related to these rights during the negotiations of the CRPD is surprising given the significant participation of persons with disabilities. Yet, despite the lack of clarification in relation to the sexual rights of persons with disabilities in the convention, the practice of interpretation of law remains a way to develop international law in this field, particularly through the evolving concept of non-discrimination.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; approches et analyses; capacitisme; cours; discipline; droit; droit des personnes en situation de handicap; droit international; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; santé; science politique et droit; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Handicap, recherche et changement social. L’émergence du paradigme émancipatoire dans l’étude de l’exclusion sociale des personnes handicapées - Boucher, Normand (Lien social et Politiques, 2003)
Le champ du handicap a subi de profondes transformations au cours des quatre dernières décennies dans la majorité des sociétés postindustrielles. Ce phénomène, qui influence les approches théoriques et la recherche à l’intérieur des sciences sociales, a fait surgir un nouveau paradigme émancipatoire basé sur une remise en cause des rapports entre le chercheur et le « sujet d’étude ». Dans cet article, nous explorons le développement de ce paradigme en nous appuyant sur l’expérience britannique, et nous discutons de son apport à la compréhension du handicap et des politiques sociales en abordant la question du rôle et de la position des acteurs au sein de la pratique de recherche
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; EDI; approches et analyses; capacitisme; corps; cours; discipline; histoire et politique; premier cycle; périodes historiques; ressource en ligne; ré; santé; sciences humaines; sex1920; sociologie; systèmes d'oppressions; thématiques; études critiques du handicap